Soft overcomes the hard: Flexible materials adapt to cell adhesion to promote cell mechanotransduction - Qian Sun (KeAi Communications Co., Ltd., 2022)
Cell behaviors and functions show distinct contrast in different mechanical microenvironment. Numerous materials with varied rigidity have been developed to mimic the interactions between cells and their surroundings. However, the conventional static materials cannot fully capture the dynamic alterations at the bio-interface, especially for the molecular motion and the local mechanical changes in nanoscale. As an alternative, flexible materials have great potential to sense and adapt to mechanical changes in such complex microenvironment. The flexible materials could promote the cellular mechanosensing by dynamically adjusting their local mechanics, topography and ligand presentation to adapt to intracellular force generation. This process enables the cells to exhibit comparable or even higher level of mechanotransduction and the downstream ‘hard’ phenotypes compared to the conventional stiff or rigid ones. Here, we highlight the relevant studies regarding the development of such adaptive materials to mediate cell behaviors across the rigidity limitation on soft substrates. The concept of ‘soft overcomes the hard’ will guide the future development and application of biological materials.